Effective control of Alphitobius diaperinus using natural bioinsecticides : Effective control of Alphitobius diaperinus using natural bioinsecticides - Niken Subekti; Shinta Hedy Cahyaningrum; Sonika Maulana (Journal of Tropical Life Science, 2022)
Pest insects known as darkling beetles (Alphitobius diaperinus) are common in poultry farms. These pests can develop into a variety of disease vectors, causing damage to chicken coops, decreased chick performance, and financial losses to farmers. In Indonesia, synthetic insecticides are still used for pest control, which is detrimental to non-target creatures and the environment. The purpose of this study is to analyze the effectiveness of biopesticides from cinnamon bark extract (Cinnamomum aromaticum), nutmeg seeds (Myristica fragrans), lavender flowers (Lavandula angustifolia), and lime peel (Citrus aurantifolia), as well as synthetic insecticides alpha-cypermethrin against A. diaperinus larvae and imago. Bioinsecticide levels are 2.5%, 5%, 7.5%, and 10%, while alpha-cypermethrin levels are 1%, 4%, 7%, and 10%, respectively, based on LC50 values. The analysis was repeated three times and the treatment was carried out every two days for a total of 14 days. The data were analyzed with paired sample t-tests to determine the average difference in each treatment when there was an average difference and calculated N-Gain score to determine the effectiveness of biopesticides and synthetic insecticides. The average value of N-Gain essential oil from cinnamon bark extract was successful in causing A.diaperinus death in the imago stage (81.14) and the highest larvae (80) of other test solutions. Cinnamon bark extract and nutmeg seed extract are effective in imago (95.14) and larvae (78.91), respectively, and can be used as a natural biopesticide to replace synthetic insecticides in the control of A.diaperinus in imago and larvae stages.